2021
DOI: 10.32404/rean.v8i1.5206
|View full text |Cite
|
Sign up to set email alerts
|

TETRAZOLIUM AND INTERACTION OF TEMPERATURE AND LIGHT UNDER SEED GERMINATION IN Ormosia arborea (FABACEAE)

Abstract: The study aimed to define the best conditions to conduct germination tests for Ormosia arborea seeds and assess the viability of seeds using the tetrazolium test. The germination tests were conducted at temperatures of 10, 15, 20, 25, 30, and 35 °C and alternating temperatures of 20-30 °C, in the presence or absence of light. For the tetrazolium test, seeds were immersed in tetrazolium solution 0.075%, at 35 °C for three hours, and then the viability was evaluated. It was verified that the seeds did not presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Most Cerrado tree species produce dormant seeds, the most common type being physically dormant seeds, especially Fabaceae (Zaidan & Carreira 2008), as in the case of O. arborea. This type of dormancy can be broken by chemical scarification resulting in rupture of the coat, allowing the entry of water and oxygen necessary to trigger the process of germination (Zaidan & Carreira 2008;Silva et al 2014Silva et al , 2021.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most Cerrado tree species produce dormant seeds, the most common type being physically dormant seeds, especially Fabaceae (Zaidan & Carreira 2008), as in the case of O. arborea. This type of dormancy can be broken by chemical scarification resulting in rupture of the coat, allowing the entry of water and oxygen necessary to trigger the process of germination (Zaidan & Carreira 2008;Silva et al 2014Silva et al , 2021.…”
Section: Discussionmentioning
confidence: 99%
“…However, in nurseries, external factors are not controlled, and the temperature of the environment may have influenced this response, because in low temperature conditions, the reorganization of cell membranes during imbibition is made difficult, making the process slower (Ferreira & Borghetti 2004), justifying increased germination response with increasing ambient temperature. It is suggested that lower temperatures are not suitable for sowing; because at a temperature of 10 °C for 120 days it did not favor the formation of O. arborea plants (Silva et al 2021), being the temperatures of 25 °C are better suited in the Cerrado and Atlantic Forest biomes species (Brancalion et al 2010). Oliveira et al (2016) verified that for O. arborea the temperature of 30 °C is better suited for germination, while 20 °C reduced the germination speed exposing the seeds for a longer period of time to adverse factors, which can lead to a reduction in total germination, vigor and/or MTE, through, for example, slower respiratory rates.…”
Section: Discussionmentioning
confidence: 99%